The Impact of Radiation Dose Variation in Panoramic Dental Examination on Salivary Amylase Enzyme Activity - Yusuf, Khalid; Milvita, Dian; Utami, Hayu Tyas (Jurusan Fisika FMIPA Universitas Andalas, 2024)
The surge in oral and dental diseases has amplified the significance of dental panoramic imaging as a diagnostic tool for healthcare professionals. However, such imaging subjects patients to radiation, impacting salivary pH and amylase enzyme activity. This study of 30 patients aimed to measure radiation doses and their effects on salivary pH and amylase enzyme activity. Radiation doses were quantified using a Thermoluminescent Dosimeter (TLD-100) and analyzed with a TLD reader. Salivary pH was determined using a digital pH meter, and amylase enzyme activity was assessed through the iodine method, involving a reaction between a 1% amylum solution, iodine solution, and saliva. Results showed an average radiation dose of 2.33 μSv, significantly affecting salivary pH. Specifically, 28 patients experienced an average pH decrease of 0.34, while 2 had an average pH increase of 0.385. These pH changes corresponded with variations in amylase enzyme activity. In 17 patients, amylase activity increased by an average of 0.75×10-4 units/mL, while 13 patients exhibited an average decrease of 0.96×10-4 units/mL. This underscores the intricate relationship between radiation dose, salivary pH, and amylase enzyme activity, warranting further exploration within dental panoramic imaging.